Blood Cell Morphology and Leukocyte Profile of the Himalayan Newt Tylototriton verrucosus Anderson, 1871 (Urodela: Salamandridae) in Thailand - Bunjerdluk, Kotchanun; Kitana, Jirarach; Pomchote, Porrawee (Tropical Natural History, 2021)
We examined the blood cell morphology and leukocyte profile in eight adult individuals (three female and five male newts) of the Himalayan newt (Tylototriton verrucosus) found at Doi Chang, Chiang Rai Province, Thailand. The hematology of T. verrucosus was found to be generally similar to other urodeles, despite small differences being observed in the cellular shape and size. The peripheral blood cells of T. verrucosus were erythrocytes, leukocytes (lymphocytes, monocytes, neutrophils, eosinophils, and basophils), and thrombocytes. The mean erythrocyte width and length was 20.18 ± 2.58 and 33.15 ± 3.91 µm, respectively. The mean diameter of the lymphocytes, monocytes, neutrophils, eosinophils, and a single basophil was 20.38 ± 3.84, 27.73 ± 4.44, 21.87 ± 2.79, 23.86 ± 3.75, and 28.62 µm, respectively. From the differential leukocyte count, the percentage of these leukocytes was 47.94, 0.44, 46.31, 5.25, and 0.06%, respectively. The mean thrombocyte width and length was 11.56 ± 1.67 and 22.62 ± 3.36 µm, respectively. This study will be used as baseline data for other hematological studies of the newt genus Tylototriton in the future.